Raised Fields of Northwestern Bolivia: a GIS based analysis - Lombardo, Umberto (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Pre-Columbian raised fields are elevated earth platforms which are found in several regions of Central and South America. The Llanos de Moxos, in lowland Bolivia, is one of the areas with the highest concentration of these earthworks. Existing studies seem to indicate that they represent a form of agricultural intensification, but the dimension of the phenomenon, field characteristics and ancient use are still little known. In this study, for the first time, satellite images are used to obtain a complete and detailed cartography of raised fi elds in an area covering 416 km2 in North Santa Ana de Yacuma. The analysis of high spatial resolution Quickbird images reveals that the amount of pre-Columbian raised fi elds in Northwestern Bolivia is far greater than what was thought to date. A detailed Geographic Information System (GIS) based analysis of the fi eld’s spatial distribution is here presented and its implication for pre-Hispanic raised fi eld management is discussed. The article will be available as a PDF in the near future.